“A letter for Dr. Outgroup”: on the effects of an indicator of competence and chances for altruism toward a member of a stigmatized out-group - Hellmann, Jens H.; Berthold, Anne; Rees, Jonas H.; Hellmann, Deborah F. (Frontiers in Psychology, 2015)
The lost letter technique is an unobtrusive method to investigate attitudes in a particular population. Ostensibly lost letters from senders who apparently belong to different groups or addressed to recipients from apparently different groups are dispersed in public places, and return rates represent a measure of altruistic or discriminatory behavior toward one group or another. In two field experiments using the lost letter technique, we investigated the influence of group membership and the presence or absence of a doctorate degree as an indicator of competence on the likelihood of receiving helping behavior. Experiment 1 showed that a generic member of a low-status ethnic out-group (Turks living in Germany) was the target of discrimination, while a generic member of a non-stigmatized out-group (French in Germany) was not. Moreover, when the name of the member from the stigmatized out-group was (vs. was not) preceded by a doctorate degree, more of the allegedly lost letters were returned. There were no such differential effects for recipients who were members of the in-group (Germans) or the non-stigmatized out-group (French). Experiment 2 showed that a recipient from the stigmatized out-group (Turk) with a doctorate degree received more letters when the sender was German versus Turkish (i.e., from the recipient’s own group). Overall, the sender’s ethnic group membership was an important factor for the likelihood of receiving an ostensibly lost letter, in that fewer letters arrived from a sender with a Turkish (vs. German) name. We conclude that the likelihood of altruistic behavior toward out-group members can increase when in-group members intend to communicate with competent out-group members. Therefore, under certain conditions, the presentation of a highly competent member of an otherwise stigmatized out-group may serve as a discrimination buffer.